Penafsiran Tauhid Emansipatoris dalam Al-Qur’an - Aqib, Ahmad (Prodi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin Institut Ilmu Al-Qur'an (IIQ) Jakarta, 2019)
In previous research, many scholars concern to study hermeneutic in Al-Qur?an such as justice, peace, equality etc. Text in Al-Qur?an always connected with social part. Term tauhid in Al-Qur?an has many meanings from clasical to contemporary meanings. The reader has differences in understanding. Because of that text has completely content and possible that there are a lot of approaching which is inter-multidisipliner. One of them is using gender approaching an analizing it is done Indonesia mufasir it self. Siti Musdah mulia try to give new colour in interprete Al-Qur?an. He share shifting paradigm analize,etimology term tauhid, and implication of spirit  equality.